1994
DOI: 10.1103/physrevlett.72.274
|View full text |Cite
|
Sign up to set email alerts
|

Bulk superconductivity at an elevated temperature (Tc≊12 K) in a nickel containing alloy system Y-Ni-B-C

Abstract: We report here our discovery of bulk superconductivity at rather high T, in samples having nominal compositions YNi4BCo, z (T, -12.5 K) and YNi&BsCo, z (T, 13.5 K). While YNi4BCo. '2 seems to be a single phase material, YNi2BSCp, q is a multiphase system, Our experimental results show that the two materials are distinct superconductors. Discovery of superconductivity in these materials is of significance since not only is their T, high (& 10 K) but they also have nickel in large proportions. No nickel-based te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
128
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 718 publications
(130 citation statements)
references
References 3 publications
1
128
0
1
Order By: Relevance
“…The non magnetic character of Ni in Bi 3 Ni is similar to that as observed earlier for the famous Ni Boro-Carbides viz. Y-Ni-B-C [15] and MgCNi 3 [16]. Detailed specific heat analysis and DFT calculations revealed that this compound is having electron-phonon coupling constant of around 1.23 and Ni is non magnetic.…”
Section: Introductionmentioning
confidence: 99%
“…The non magnetic character of Ni in Bi 3 Ni is similar to that as observed earlier for the famous Ni Boro-Carbides viz. Y-Ni-B-C [15] and MgCNi 3 [16]. Detailed specific heat analysis and DFT calculations revealed that this compound is having electron-phonon coupling constant of around 1.23 and Ni is non magnetic.…”
Section: Introductionmentioning
confidence: 99%
“…Because it has a large proportion of Ni per unit cell, it is expected that the magnetic fluctuation would be important in determining the superconducting behavior. This system is reminiscent of another Ni-based superconductors LnNi 2 B 2 C (Ln = Y, Tm, Er, Ho, Lu) [2][3][4] . The band calculations indicate that very large and narrow energy peak in the density of states (DOS) is located just below the Fermi energy E F which has mainly the Ni 3d character 5,6 .…”
mentioning
confidence: 99%
“…Since the pioneering and seminal discovery of the superconducting alloy system Y-Ni-B-C [1,2] by Nagarajan et al, much attention has been paid to synthesizing single phase samples of quaternary boro-carbides. Cava et al [3] have synthesized the quaternary nickel borocarbides RNi 2 B 2 C (R=Y and rare earths), and found that Lu and Y compounds exhibit the highest superconducting transition temperatures (T c = 16.6 and 15.6 K, respectively), while compounds with magetic rare earths exhibit lower T c : T m (T c = 11 K), E r (T c = 10.5 K), H o (T c = 8 K).…”
Section: Introductionmentioning
confidence: 99%